One Health clinic challenges and evolution: increasing access to care for people and pets in a rural community in Northern California - Jankowski, Kristin; Aguirre Siliezar, Kimberly; Knuchell, Jeannie A.; Duenas-Ramirez, Adrian; Edwards, Jennifer J.; Dear, Jonathan D. (Frontiers in Veterinary Science, 2025)
A student-run, free One Health clinic (OHC) improves access to care for people and pets while providing increased training opportunities for interprofessional students in the areas of spectrum of care, contextualized care, cultural humility, ethical community engagement, and relationship-centered communication when clinical instruction is provided. The coordination and implementation of a community-based student-run free clinic (SRFC) that is also an OHC is complex. Programmatic challenges can include coordination with the leaders of multiple training programs, seasonal variation of student and clinical instructor schedules, and the need to balance student experiential learning with positive client and patient outcomes. Internal evaluations of the clinic's scope of care, patient and provider safety, and student preparedness has led to the development of policies and procedures that consider both student training and the client-patient experience. Widening the OHC provider and student partnership to include human nursing was a novel and effective method to enhance care for the bonded family and create opportunities for interprofessional education (IPE) for students from multiple training programs at a single clinical site.